Modelling the thermal, electrical and flow profiles in a 6-in-line matte melting furnace - Snyders, Cornelius Albert (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Process Engineering))--Stellenbosch University, 2008.